ANATOMY OF THE DARK SIDE OF GOVERNANCE:: BETWEEN FORMAL LEGALITY AND TRANSACTIONAL REALITY - Maisondra Maisondra; Fifian Adeningsi Mus (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
This research dissects the phenomenon of bureaucratic pathology in Indonesia through the concept of the "dark side" of governance—specifically, the use of formal legal instruments to validate corrupt transactional practices. Departing from previous studies that have predominantly viewed maladministration as mere technical-administrative failure or conventional corruption, this research offers a scholarly contribution (novelty) through the theoretical framework of "Sociological Constitutionalism Based on Local Wisdom." This approach shifts the paradigm from top-down, legal-formal supervision toward the integration of socio-cultural sanctions as an informal control mechanism to counter state capture. Utilizing a qualitative method with a normative-empirical approach, this research analyzes the shift from Rule of Law to Rule by Law, as well as the exploitation of administrative discretion arising from hyper-regulation in the digital era. The primary academic contribution of this article is a proposed mitigation model for maladministration that no longer relies solely on bureaucratic digitalization as a panacea, but emphasizes the synchronization of procedural rigidity with societal ethical values as a counterweight to oligarchic power. The analysis demonstrates that without a reorientation of bureaucratic ethics grounded in local sociological values, digitalization will remain merely a procedural cosmetic that perpetuates state capture corruption behind the facade of government modernization.